A chimpanzee’s time to feast: seasonality of Macrotermes flight hole activity and alate dispersal flights detected by termite-fishing experiments and camera traps in the Issa Valley, Tanzania - Phillips, Seth; Piel, Alex K.; Stewart, Fiona A.; Oelze, Vicky M. (Frontiers in Ecology and Evolution, 2023)
Investigation into chimpanzee termite-fishing behavior has provided invaluable insights into the evolution of animal tool use and culture. However, research to date often overlooks how the ecology of termites may shape the nature of this predator-prey interaction. Though anecdotal links between meteorological factors, termite dispersal flights and the ability of chimpanzees to termite-fish have been made, these relationships were never empirically tested. In this study, we examined if and how the reproductive ecology of mound building termites (Macrotermes subhyalinus) affects the availability of this resource to termite-fishing chimpanzees in the Issa Valley, Tanzania. We utilized in-person termite-fishing experiments, remote camera trap footage, as well as meteorological data to model both the availability of termite prey across seasons for chimpanzees as well as the timing of dispersal flights of the termite reproductive caste (alates). Additionally, we describe the predator diversity that characterizes alate swarming events during their seasonal dispersal flights. We identify strong relationships between meteorological factors, Macrotermes alate dispersal flights and vulnerability of the colony to predation. As rainfall accumulates, Macrotermes become more abundant in their flight holes and are thus more vulnerable to researcher termite-fishing experiments. This increased accessibility to Macrotermes continues until alate dispersal flights which we also find are linked to cumulative rainfall as well as negatively correlated to wind speed. This type of baseline data on Macrotermes ecology is fundamental when forming hypotheses and designing studies into topics such as chimpanzee culture, tool-use, and foraging cognition.